Three-dimensional consolidation theory of vertical drain based on continuous drainage boundary - Zhang, Yi; Wu, Wenbing; Mei, Guoxiong; Duan, Longchen (Journal of Civil Engineering and Management, 2019)
To remedy the limitation that the conventional drainage boundary only considers two extreme cases of pervious and impervious boundaries, the consolidation theory of vertical drain is derived by applying the continuous drainage boundary, and its validity is also proven. Based on the obtained solutions, the excess pore water pressure and the average degree of consolidation under the continuous drainage boundary condition are analyzed, and the effect of the drainage capacity of the top surface, the smear effect and the well resistance on consolidation are explored. Furthermore, the practicality of this theory is also validated by the comparison with experimental data. Results confirm that the complete and continuous process of the ground top surface can be changed from no drainage to a complete drainage by adjusting the value of the interface parameter b. Higher value of the interface parameter b means a stronger water permeability of the foundation, resulting in a faster dissipation of excess pore water pressure and a faster consolidation. Meanwhile, the vertical drainage of the vertical drain cannot be neglected in calculation even though vertical drains are based on a horizontal seepage. Moreover, the smear effect and the well resistance play an important role on consolidation.